How Do I Know Whether to Trust a Research Result? - Shepperd, Martin (IEEE software, 2015)
A meta-analysis indicated that some areas of computer science research are subject to researcher bias. However, rather than mistrust all scientific research, researchers should examine research to determine its validity.